Randomized double‐blind comparison of the effects of intramyometrial and intravenous oxytocin during elective cesarean section. Issue 4 (20th January 2016) - Akinaga, Chieko; Uchizaki, Sakiko; Kurita, Tadayoshi; Taniguchi, Mizuki; Makino, Hiroshi; Suzuki, Akira; Uchida, Toshiyuki; Suzuki, Kazunao; Itoh, Hiroaki; Tani, Shigeki; Sato, Shigehito; Terui, Katsuo
Abstract: Aim: Obstetricians sometimes administer intramyometrial oxytocin to stimulate uterine contraction during cesarean section, but its effects have not been well investigated. We performed a randomized, double‐blind study to test the hypothesis that a small dose of intramyometrial oxytocin would induce acceptable uterine contractility more quickly and with fewer hemodynamic side‐effects than the same dose administered intravenously. Methods: Forty women with a single fetus at ≥36 weeks of gestational age scheduled for elective cesarean section under spinal anesthesia were randomized to the intravenous and intramyometrial groups to receive oxytocin at 0.07 IU/kg. The drug was administered immediately after umbilical cord clamping. Systolic blood pressure, heart rate, intraoperative blood loss, uterine tone, total amount of intraoperative oxytocin, and additional uterotonic drugs administered in the first 24 h were compared. Results: Maximum uterine contractility was achieved after 2 and 10 min for the intravenous and intramyometrial groups, respectively. The mean hemodynamic parameters of the intramyometrial group were stable. In contrast, the intravenous group showed a reduction in systolic blood pressure after 2–4 min and increased heart rate after 1–2 min. Intraoperative blood loss, total oxytocin dose, and frequency of additional uterotonic drugs were comparable between the two groups. Conclusion: Although intraoperative blood loss was comparable, a small dose of intramyometrial oxytocin was inappropriate to obtain a prompt and acceptable uterine contraction during cesarean section.